2021
DOI: 10.3389/fgene.2021.758926
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA Methylation Molecular Features for Diagnosis and Prognosis in Gastric Cancer

Abstract: Background: The management of gastric cancer (GC) still lacks tumor markers with high specificity and sensitivity. The goal of current research is to find effective diagnostic and prognostic markers and to clarify their related mechanisms.Methods: In this study, we integrated GC DNA methylation data from publicly available datasets obtained from TCGA and GEO databases, and applied random forest and LASSO analysis methods to screen reliable differential methylation sites (DMSs) for GC diagnosis. We constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In addition, in multiple cancers, DNA methylation throughout the genome is an epigenetic modification contributing to the regulation of cancer-associated genes ( Liu D et al, 2021 ; Rogozin et al, 2021 ). Research studies have verified that PDK4 methylation could display the oncogenic roles in colon cancer ( Leclerc et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in multiple cancers, DNA methylation throughout the genome is an epigenetic modification contributing to the regulation of cancer-associated genes ( Liu D et al, 2021 ; Rogozin et al, 2021 ). Research studies have verified that PDK4 methylation could display the oncogenic roles in colon cancer ( Leclerc et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous types of research have indicated that DNA methylation, as an epigenetic modification, contributed to regulating the expression of cancer-related genes. [ 31 ] Thus, the promoter methylation level of CDKN2A between tumors and normal tissues was explored via the “CPTAC” dataset. As displayed in Figure 6 A, compared with normal samples, the promoter methylation level of CDKN2A was dramatically increased in most cancers (e.g., BLCA, COAD, KIRC, LIHC, and so on), except KIRP with decreased methylation level.…”
Section: Resultsmentioning
confidence: 99%
“…As an epigenetic modification, DNA methylation contributes to regulating the expression of cancer-related genes. [ 31 ] A meta-analysis performed by Zhou pointed out that CDKN2A methylation had a crucial role in the occurrence of esophageal cancer. [ 41 ] However, Cao et al indicated that CDKN2A methylation was not significantly correlated with the progression of PRAD.…”
Section: Discussionmentioning
confidence: 99%
“…More and more corroboration alludes to a crucial role for aberrant DNA methylation in the initiation and development of GC. [25][26][27][28] To begin our investigation, we used Pearson coefficients to see if the JAM3 methylation status affected JAM3 mRNA expression. In GC tissues, a strong inverse connection was seen between JAM3 methylation and JAM3 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%